LARGE SCALE VERTICAL ELECTRICAL SOUNDINGS SURVEY IN ANTHEMOUNTAS RIVER BASIN FOR EVALUATING HYDRAULIC COMMUNICATION BETWEEN SUB BASIN AQUIFERS - Vargemezis, G.; Fikos, I. (Bulletin of the Geological Society of Greece, 2010)
In Anthemountas river basin a number of studies have taken place mainly because of the significant drop of underground water level observed in the beginning of the last decade. Data from existing hydrowells show the existence of a complex aquifer with the two main underground water bodies situated east and west of the region of Vasilika and Galarinos villages respectively. A large scale geophysical survey took place consisting of Vertical Electrical Soundings (VES) and Electrical Resistivity Tomography (ERT). The main area of interest is in the central region of the basin between Vasilika and Galarinos villages where eighty five (85) VES (Schlumberger array), located on a regular grid revealed a three dimensional model for the sedimentary formations while mapping the bedrock down to a depth of more than 600m has been achieved. In the same area, ERT measurements and geological information derived from borehole data are used to obtain a more detailed geological model for the area of interest. From surface to bedrock depth, the hydraulic communication between these two water bodies is examined. Furthermore significant geological features are observed and discussed.